# 41p+37p+3pqr=

## Simple and best practice solution for 41p+37p+3pqr= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 41p+37p+3pqr= equation:

Simplifying
41p + 37p + 3pqr = 0

Combine like terms: 41p + 37p = 78p
78p + 3pqr = 0

Solving
78p + 3pqr = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), '3p'.
3p(26 + qr) = 0

Ignore the factor 3.
Subproblem 1Set the factor 'p' equal to zero and attempt to solve:

Simplifying
p = 0

Solving
p = 0

Move all terms containing p to the left, all other terms to the right.

Simplifying
p = 0
Subproblem 2Set the factor '(26 + qr)' equal to zero and attempt to solve:

Simplifying
26 + qr = 0

Solving
26 + qr = 0

Move all terms containing p to the left, all other terms to the right.

Add '-26' to each side of the equation.
26 + -26 + qr = 0 + -26

Combine like terms: 26 + -26 = 0
0 + qr = 0 + -26
qr = 0 + -26

Combine like terms: 0 + -26 = -26
qr = -26

Add '-1qr' to each side of the equation.
qr + -1qr = -26 + -1qr

Combine like terms: qr + -1qr = 0
0 = -26 + -1qr

Simplifying
0 = -26 + -1qr

The solution to this equation could not be determined.

This subproblem is being ignored because a solution could not be determined.Solutionp = {0}`